Virtual Differentiated Instructions: Effects on English Language Proficiency of Grade 9 Students - Mark Anthony C. Pasubillo; Asio, John Mark R. (Contemporary Journal of Applied Sciences, 2023)
The objective of this study is to determine the English language proficiency level and effects of virtual differentiated instruction to Grade 9 students from a Science high school in Olongapo City, Philippines. This study used a quasi-experimental (pretest-posttest) design to 143 purposively selected Grade 9 students. Then, the study used a paired t-test to analyze the data gathered. The study provided a substantial evidence that virtual differentiated instruction has significant effect on the English language proficiency of the students. Hence, the utilization of virtual differentiated instructions to improve the English proficiency of the respondents is effective and beneficial